The Investigation of Machinability and Surface Properties of Aluminium Alloy Matrix Composites - Priyadarsini Morampudi; Venkata Ramana V.S.N.; Koona Bhavani; Amrita M; V Srinivas (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Aluminum matrix composites (AMCs) are crucial to the progress of composite application areas due to their remarkable mechanical properties. Their usage has expanded into different fields such as the aerospace, automobile, and defense industries. The present study used wrought Al alloy AA6061 as the matrix, while ilmenite (FeTiO3) particles were used as reinforcement at different weight percentages to prepare metal matrix composites. One of the most economical and simple casting routes among the several available fabrication techniques for the preparation of composites is the stir casting method, which was applied in the present investigation to prepare the AMCs. The machinability of the fabricated composites and the surface roughness property after machining were studied to understand the effect of speed and feed during machining. The results showed that an increase in speed decreased the cutting forces and the surface roughness. Meanwhile, an increase in surface roughness was observed with an increase in feed.